Transformasi Digital Perbankan Konvensional (Kajian empiris tantangan pada perbankan Syariah) - Taswiyah - Taswiyah (FEB Universitas Sultan Ageng Tirtayasa, 2022)
Digital transformation is widely discussed along with the industrial revolution 4.0 and leads to society 5.0. This research is descriptive qualitative using content analysis techniques and literature studies based on reference sources, reference books, proceedings, national/accredited journals, and international and reputable journals. With the object of study digital transformational practices at BRI, BNI, and BTPN Bank which can be used as a reference to be applied to the transformational digital sharia banking